Can't and won't - Davis, Lydia, 1947- (Farrar, Straus and Giroux, 2014)
A fifth collection by the author of the National Book Award finalist, Varieties of Disturbance, includes pithy one-liners, exploratory observations and letters of complaint, including "A Small Story About a Small Box of Chocolates," in which a professor is stymied by her choices.